1983
DOI: 10.1001/archotol.1983.00800250029007
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration in Squamous Cell Carcinoma of the Head and Neck

Abstract: \s=b\Cytological examination of fine-needle aspiration (FNA) specimens from patients with known or suspected squamous cell carcinoma of the head and neck at the University of Virginia, Charlottesville, between 1979 and reviewed. Of 229 aspirates, 187 were of cervical or submandibular sites and 42 were of oral cavity sites. The accuracy of cytological diagnoses was determined by histological comparison and clinical follow-up. There were no false-positive aspirates (specificity, 100%) and one false\x=req-\ negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
5

Year Published

1985
1985
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 24 publications
1
18
0
5
Order By: Relevance
“…We believe, however, that a negative result of cytologic examination is almost as reliable as a positive one. This statement is based on high sensitivity, specificity and negative predictive value of UGFNAB in our study, and high accuracy of cytologic examination in other studies [20][21][22], It is on grounds of the above-men tioned studies and a previous study [8], that it seems justi fied to consider palpable nodes benign when the cytologic diagnosis is negative. This may lead to down-staging of a considerable proportion of the patients.…”
Section: Possible Effects Of Negative Results Of Ultrasound With Ugfnsupporting
confidence: 62%
“…We believe, however, that a negative result of cytologic examination is almost as reliable as a positive one. This statement is based on high sensitivity, specificity and negative predictive value of UGFNAB in our study, and high accuracy of cytologic examination in other studies [20][21][22], It is on grounds of the above-men tioned studies and a previous study [8], that it seems justi fied to consider palpable nodes benign when the cytologic diagnosis is negative. This may lead to down-staging of a considerable proportion of the patients.…”
Section: Possible Effects Of Negative Results Of Ultrasound With Ugfnsupporting
confidence: 62%
“…It may be helpful only in a few cases where it may allow for a specific diagnosis, such as a tuberculosis or syphilis, and make biopsy avoidable [8], FNA may also be useful in patients presenting a recurrent malignant mass, where it may make a biopsy unnecessary and obviate poor wound healing after radiation [1,8], However, in these cases, smears frequently do not yield satisfactory material due to excessive fibrosis caused by previous treatments. Other wise, excisional biopsy of the mass under general anesthe sia with a frozen section followed by a neck dissection, if necessary, is more effective.…”
Section: ]mentioning
confidence: 99%
“…Fine-needle aspiration biopsy (FNA) represents a diag nostic examination which has gained popularity during the last 2 decades [1][2][3][4], In some clinics, FNA is used today systematically for the initial workup of every pa tient with a lump in the head and neck [5][6][7]. In 1990, we reported the results of 150 FNAs [8] and concluded that there is no reason in terms of efficiency and reliability to justify systematic FN A .…”
Section: Introductionmentioning
confidence: 99%
“…In the head and neck region FNAB provides an alternative to premature open biopsy of masses in the neck, which is especially ill-advised in case of neck nodes in patients with occult squamous cell carcinoma of the upper aero-digestive tract [2,3]. The risk of tumor seeding in the tract of the needle is negligible [4][5][6].…”
Section: The Thyroid Regionmentioning
confidence: 99%